2017
DOI: 10.1007/s00592-017-0972-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-related burden and distress in people with diabetes mellitus at primary care level in Germany

Abstract: Only 1.2% of our outpatients with diabetes on primary care level showed high diabetes-related distress. Higher rates in the current literature are probably due to not investigating on primary care level. Guidelines should consider this.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 24 publications
4
21
1
4
Order By: Relevance
“…It was noted that those who had high levels of DDS had poor glycemic control. Similar finding was also observed in other populations (Islam et al, 2013;Kuniss et al, 2017;Aljuaid et al, 2018). Diabetes related distress generally shows a closer association with glycemic control.…”
Section: Discussionsupporting
confidence: 89%
“…It was noted that those who had high levels of DDS had poor glycemic control. Similar finding was also observed in other populations (Islam et al, 2013;Kuniss et al, 2017;Aljuaid et al, 2018). Diabetes related distress generally shows a closer association with glycemic control.…”
Section: Discussionsupporting
confidence: 89%
“…Conversely, a study in Germany conducted at a tertiary care facility reported the prevalence of DRD was 8.9% using the Problem Area in Diabetes (PAID) questionnaire, the same level found in this study. However, another German study conducted at the primary care level reported only a 1.2% prevalence of DRD using the PAID scale [39,40]. The differences in DRD prevalence might result from differences in the assessment tools, i.e., the PAID and the DDS-17 questionnaires, which could potentially affect prevalence, e.g., sample size, access to health care, care setting [39], and demographic variables, e.g., education level and family support, as well as health status, e.g., HbA1c level, and co-morbidity [24,41,42].…”
Section: Discussionmentioning
confidence: 96%
“…The differences in DRD prevalence might result from differences in the assessment tools, i.e., the PAID and the DDS-17 questionnaires, which could potentially affect prevalence, e.g., sample size, access to health care, care setting [39], and demographic variables, e.g., education level and family support, as well as health status, e.g., HbA1c level, and co-morbidity [24,41,42]. The findings of these studies are consistent with our finding that DRD prevalence is higher in people with type 2 diabetes treated in a secondary and tertiary care setting than in those treated in a primary care setting [39,43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, distress proportions were 48.5%, 43%, and 39% in three different studies using DDS-17 from Bangladesh, China, and Canada, respectively [ 11 13 ]. On the other hand, two studies from Germany used Problem Areas in Diabetes Questionnaire (PAID) to show that 8.9% and 10.7% of their sample were distressed [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%